1997
DOI: 10.1002/(sici)1096-9861(19970630)383:2<163::aid-cne4>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic and other noncholinergic basal forebrain neurons, together with cholinergic neurons, project to the mesocortex and isocortex in the rat

Abstract: The extrathalamic relay from the brainstem reticular formation to the cerebral cortex in the basal forebrain has been thought to be constituted predominantly, if not exclusively, by cholinergic neurons. In contrast, the septohippocampal projection has been shown to contain an important contingent of gamma-aminobutyric acid (GABA)ergic neurons. In the present study, we investigated whether GABAergic neurons also contribute to the projection from the basal forebrain to neocortical regions, including the mesocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(161 citation statements)
references
References 51 publications
10
150
0
Order By: Relevance
“…Some orexin-positive projections to the basal forebrain appear to form synapses onto neurons that were not immunopositive for choline acetyltransferase (Fadel et al 2005). Many of these neurons appear to be magnocellular and parvalbuminimmunoreactive (unpublished data) suggesting that they may contribute to the GABAergic component of the basalocortical projection system (Gritti et al 1993(Gritti et al , 1997Zaborszky et al 1997). In summary, the present experiments provide evidence that orexin-1 receptor blockade can disrupt accuracy in the present attention-demanding task, but clearly, additional work is needed to identify the mechanisms underlying the observed accuracy impairments.…”
Section: Discussionsupporting
confidence: 83%
“…Some orexin-positive projections to the basal forebrain appear to form synapses onto neurons that were not immunopositive for choline acetyltransferase (Fadel et al 2005). Many of these neurons appear to be magnocellular and parvalbuminimmunoreactive (unpublished data) suggesting that they may contribute to the GABAergic component of the basalocortical projection system (Gritti et al 1993(Gritti et al , 1997Zaborszky et al 1997). In summary, the present experiments provide evidence that orexin-1 receptor blockade can disrupt accuracy in the present attention-demanding task, but clearly, additional work is needed to identify the mechanisms underlying the observed accuracy impairments.…”
Section: Discussionsupporting
confidence: 83%
“…The mice in which injections had produced labeled axons in the medial pathways also showed a strong innervation of superficial layers in IL, PL, and ACv, suggesting that cholinergic fibers arrive via different routes in the superficial and deep layers in the mPFC regions. Previous work has studied the topographic mapping of the cholinergic system using a combination of retrograde tracing with post hoc immunohistochemical identification (Bigl et al, 1982;Price and Stern, 1983;Zaborszky et al, 1986Zaborszky et al, , 1999Gritti et al, 1997Gritti et al, , 2003. Although these studies have provided a wealth of knowledge and have demonstrated a mapping of neurons in the basal forebrain to discrete regions in the cortex, they have mainly focused on the innervation of large cortical areas that were located far apart.…”
Section: Discussionmentioning
confidence: 99%
“…When recorded in head-restrained rats, neurons that were immunohistochemically identified as cholinergic cells discharged in bursts during waking and REMS, and fell silent during NREMS [38]. However, of BF neurons projecting to the cortex more are GABAergic than cholinergic in the rat [39]. Of those projecting to the wake-regulating lateral hypothalamus, half can be considered GABAergic, about 25% glutamatergic and only 10% cholinergic [40].…”
Section: Basal Forebrain and Anterior Hypothalamic Neuronal Groups Inmentioning
confidence: 99%